The Representation of Social, Economic, Psychological, and Reproductive Health Condition of the Commercial Sex Workers Post-closing of the Dolly Complex in Surabaya - Danty Indra Puspitaningtyas; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Dolly was the biggest red light district in Southeast Asia with more than 1000 (a thousand) women working as commercial sex workers. Because the district imposed a very negative effect to the surrounding inhabitants especially to children, therefore red light district area of Dolly and Jarak which are located in residential area had to be closed. The quality of life of the residents especially the commercial sex workers was very much affected after the district was closed. The study aimed to understand the representation of the social, economic, psychological, and reproductive health condition after the Dolly district in Surabaya was closed.Subject and Method: This was a qualitative descriptive study with phenomenology approach. This study was conducted in former red light districts of Dolly and Jarak in Surabaya from January 18-February 28, 2017. The informant of this study were commercial sex workers, former commercial sex workers, head of hamlet (RW), former pander of Dolly, Head of Civil Society Organization, healthcare workers, and Social Office of Surabaya City. The sampling technique used was snowball sampling, with in-depth interviews, observation, documentation study. The data were analyzed by interactive analysis model including data collection, data reduction, display and verification. Results: The commercial sex workers characteristic prior and post closing of the district were around 28-43 years old, with elementary – senior high school educated. Most of the commercial sex workers were from outside the city with 1-5 customers/day. They charged Rp. 100-300 thousand (Dolly’s commercial sex workers) per customer and Rp. 100-200 thousand/customer (Jarak’s commercial sex workers). The representation of quality of life post-closing was poor, altered social condition, lack of interaction with others, the degradation of economic condition, poor psychological condition due to the economical problem, and reproductive health was less protected because they did not get regular examination like before the complex was closed.Conclusion: The representation of quality of life in terms of the condition of social, economic, psychology, and reproductive health of the commercial sex workers post Dolly and Jarak closing were poor. Therefore, government intervention was very much needed to help improving the quality of life of the commercial sex workers.Keywords: Commercial sex workers, social, economic, psychological, reproductive health.Correspondence: Danty Indra Puspitaningtyas. Masters Program of Public Health, Sebelas Maret University, Surakarta. Email: dantyindra@yahoo.com. Mobile: +6285732850663Journal of Health Promotion and Behavior (2017), 2(1): 77-87https://doi.org/10.26911/thejhpb.2017.02.01.07